Knowledge of Basic Life Support (BLS) for High School Students - Ndruru, Anita; Sitindaon, Sry Rumondang; Mendrofa, Deskrisman Stefan (Jurnal EduHealth, 2025)
BLS is a first aid measure for victims who experience cardiac arrest and respiratory arrest. This includes identifying the person in cardiac arrest, calling an ambulance and performing cardiopulmonary resuscitation, and being able to use an Automated External Defibrillator (AED) to assist the victim. Knowledge of Basic Life Support (BLS) is very important for high school students as an effort to improve preparedness in dealing with emergency conditions. The purpose of this study to determine the overview of high school students knowledge about BLS. The method used is descriptive survey with cross sectional approach. Data collection was obtained through the distribution of questionnaires to 36 samples of SMA Era Utama. The results found that the average knowledge of SMA Era Utama about BLS is as much as 39.02. So in this case, the majority of SMA Era Utama do not know about basic life support (BLS). This study suggests the need for greater integration of BLS at the high school level and increased access to practical training for students to improve their preparedness for emergency situations, especially in victims of cardiac arrest.